Effective stripping and reutilization of LiFePO4 cathode waste from retired lithium ion batteries. Issue 6 (15th March 2023) - Zhang, Yucai; Yao, Xiang; Che, Yuanyuan; Gao, Ziwei; Su, Zhi
Abstract: The recycling of retired lithium ion batteries (LIBs) plays a vital role in alleviating the energy crisis and preventing secondary pollution. However, the unstable properties of waste materials greatly restricts the reuse of recycled materials in the industrial energy domain. Herein, we applied water as stripping solvent to effectively dispose of lithium iron phosphate (LiFePO4 ) cathode scrap. The results showed that the stripping rate of cathode scrap could reach more than 92%, and the recycling did not give rise to any impact on the structure of the cathode material under optimized condition. The molar ratios of elements were signed as n (Li): n (Fe): n (P) = 5 : 4.6: 4.95 by inductively coupled plasma emission spectroscopy (ICP-OES) and energy disperse spectroscopy (EDS). The Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) showed that the PVDF was completely invisible after sintering. The LiFePO4 materials calcined at different temperature for 10 h under argon atmosphere showed excellent constant current charge-discharge performance and good cycle life, which reflected the stability of the olivine structure. The LiFePO4 cathode material directly calcined at 650 °C for 10 h exhibited the best charge-discharge specific capacity with a high Coulombic efficiency of 99.2%. Cyclic voltammetry (CV) tests showed that the re-sintered LiFePO4 material had a less redox polarized potential compared with the retired LiFePO4 material. The non-structure-damaging recycling mode also provides a green and effective direction for the recovery and recyclability of retired LiFePO4 . Graphical abstract: The discharge capacity of the recycled sample LFP-650-10 was 164.2 mA h g −1 at first cycle, and it could deliver a discharge capacity of 161.9 mA h g −1 after 100 cycles with a high capacity retention of 98.5%. Image 1